Abundance of Bering-Chukchi-Beaufort bowhead whales (Balaena mysticetus) in 2004 estimated from photo-identification data - Koski, W. R.; Zeh, J.; Mocklin, J.; Davis, A. R.; Rugh, D. J.; George, J. C.; Suydam, R. (J. Cetacean Res. Manage., 2023)
Ice-based surveys near Point Barrow, Alaska, have been used to obtain most estimates of abundance for the Bering-Chukchi-Beaufort (B-C-B) stock of bowhead whales, but global warming has raised concerns that ice-based surveys may not be practical in the future. Aerial photographic surveys provide an alternative method for obtaining abundance estimates and may replace ice-based surveys. Aerial photographic surveys were conducted near Point Barrow during the spring migrations of bowhead whales in 2003 and 2004 and, in 2005, in the northern Bering Sea in spring and near Barrow in fall. The 2003 survey was the most complete photographic survey of the population conducted to date. These surveys provided photo-identification data for use in capture-recapture analyses. A screening procedure was used to define which whales captured in 2003, 2004 and/or 2005 were marked and could be reidentified if photographed on another occasion. An estimate of the number of marked whales was obtained using a closed population model for capture-recapture data. Several models were investigated, including models that accounted for heterogeneity in capture probabilities, but a simple model with no covariates produced the most precise estimate. To account for unmarked whales, the estimate of marked whales was divided by an estimate of the proportion of the bowhead population that was marked based on the 1989–2004 spring photographic surveys near Point Barrow. Abundance of the B-C-B bowhead population in 2004 (excluding calves) was estimated to be 12,631 with CV 0.2442, 95% bootstrap percentile confidence interval (7,900; 19,700) and 5% lower limit 8,400. These results were compared with results that used approximate variance expressions for the estimates of the number of marked whales, the proportion of the population that was marked and population abundance instead of using the bootstrap. The estimates of abundance in 2004 computed for comparison included one based on a modified Petersen estimate of the number of marked whales that omitted the 2005 data as well as the estimate of 12,631 described above. The comparison estimates also included estimates of abundance in 1985 computed from 1984–87 photographic survey data using the same methods. All the abundance estimates computed from photographic data were consistent with expectations based on independent abundance and trend estimates from the ice-based surveys conducted from 1978 to 2001.